Feminism and the dialectic of the private and the absolute In the narrative film Hidden fingers film as a model (Journal of the College of Basic Education, 2022)
The cinema, which emphasizes its female heroines, has been preoccupied with showing the mother heroine, the working heroine, the heroine who is subjected to domestic and racist violence, the artist heroine, the novelist, the fighter, and so on. A good film is one that seeks to make its heroine a heroine that can be generalized to become a cosmic heroine, transcending her locality and privacy, towards global horizons with the power of art and model that considers multiculturalism as rich for the human kind, so that this heroine can inspire women and men around the world to confront their destiny and change it towards The best or share that heroine through the future horizons that art offers to people.